Contralateral Lower Neck Sparing Radiotherapy in Stage N1 Nasopharyngeal Carcinoma: Long-Term Survival Outcomes and Late Toxicities - Sun, Zhuang; Wang, Jingyun; Huang, Runda; Wang, Xiaohui; Chen, Chunyan; Deng, Meiling; Zhao, Chong; Wang, Hanyu; Han, Fei (Frontiers in Oncology, 2021)
Purpose：To explore the feasibility of contralateral lower neck sparing radiotherapy for patients with stage N1 nasopharyngeal carcinoma (NPC) by analyzing long-term survival outcomes and late toxicities. Methods：Data of patients with stage N1 NPC who were treated with contralateral lower neck sparing radiotherapy between January 2013 and December 2015 were analyzed. These patients were all staged by magnetic resonance imaging (MRI) and all received irradiation to the upper neck (levels II, III, and Va) bilaterally along with ipsilateral levels IV and Vb, without irradiation of the contralateral lower neck. Treatment outcomes, regional failure patterns, and late toxicities were examined. Results：A total of 275 eligible patients with stage N1 NPC were included in the present study. The median follow-up period was 62 months (range, 3–93 months). The 5-year overall survival (OS), distant metastasis-free survival (DMFS), local recurrence-free survival (LRFS), regional recurrence-free survival (RRFS), locoregional recurrence-free survival (LRRFS), and progression-free survival (PFS) rates were 90.5%, 91.3%, 94.7%, 95.3%, 91.2%, and 81.7%, respectively. A total of 13 patients (4.7%) developed regional recurrence, all of which occurred in the field and not out of the field. Among 254 patients with available data on late toxicities, the most common late toxicity was xerostomia. No late injuries occurred in the carotid arteries, brachial plexus, or spinal cord. In addition to 1 case (0.4%) of neck fibrosis and 3 cases (1.2%) of hearing loss, there were no other grade 3–4 late toxicities observed. Conclusions：Contralateral lower neck sparing radiotherapy would be safe and feasible for patients with stage N1 NPC, with the potential to improve the long-term quality of life of patients.